Vendetta : Lucky's Revenge - Collins, Jackie (London PAN Books, 1997)
Features Lucky Santangelo from "Chances", "Lucky" and "Lady Boss". In "Lady Boss", Lucky bought Panther Studios. Here, her studios are taken from her by Dona Landsman - the scheming widow of the Santangelo's arch enemy, Santino Bonnati. And now Lucky - never a girl to give up - is out for revenge.
Keywords: Motion Picture Industry -- California--Los Angeles